Analisis Korelasi Usia, Massa Tubuh, mAs, dan Dosis Efektif Terhadap CTDIvol dan DLP pada Pemeriksaan CT-Scan Pasien Dewasa - Wafi Muthia Dewanti; Ida Bagus Gede Putra Pratama; Sri Herlinda; Dian Milvita; Ramacos Fardela (Jurnal Fisika Unand, 2024)
A research study has been conducted on the correlation analysis of age, body mass, mAs, and effective dose with Computed Tomography Dose Index Volume (CTDIvol) and Dose Length Product (DLP) in CT-Scan examinations at the Radiology Department of Dr. M. Djamil Padang General Hospital. The research utilized data from adult patients aged 15 years and above with a standard body mass (60 ± 10) kg in non-contrast CT scans of the head, chest, and abdomen, with a total of 586 patients collected over a period of 3 months. The analysis was conducted using Pearson correlation test. The research results indicate that the effective dose has a very high correlation with DLP, with a coefficient of 1 and mAs has a very high correlation with CTDIvol and DLP, with a coefficient of 0,9. Body mass has a relatively high correlation with CTDIvol and DLP, ranging from 0,4 to 0,7 except in head examinations. Age has a moderately significant correlation with CTDIvol and DLP, ranging from 0,1 to 0,5.